Efektivitas pembelajaran daring di masa pandemi Covid-19 terhadap hasil belajar siswa SD - Wardaini, Dina Oktaviana (Educenter : Jurnal Ilmiah Pendidikan, 2022)
The development of education today is influenced by the rapid progress of information and communication technology. One of the information technologies that play a role in the world of education is online learning. Online learning functions as a liaison between educators and students with an internet network that can be accessed anytime and anywhere. The online media used by the research subjects are various (WhatsApp, Google Classroom, Website). The purpose of this study was to analyze the effectiveness of online learning applied to the elementary school level. The method collected in data collection was a question and answer session with the sources, namely elementary school students via WhatsApp and the results of observations made by researchers during online learning. Looking at the results of student learning in elementary school, it can be concluded that online learning can be said to be effective and the material delivered by the teacher is maximal if it is accompanied by parents.